Multiple pathways to conservation success. Issue 2 (25th October 2012) - Phillis, Corey C.; O'Regan, Sacha M.; Green, Stephanie J.; Bruce, Jeanette E.B.; Anderson, Sean C.; Linton, Jennifer N.; ,; Favaro, Brett
Abstract Conservation successes can and do happen, however, the process by which society achieves them remains unclear. Using a novel culturomics approach, we analyse word usage within digitized texts to assess the chronological order in which scientists, the public, and policymakers engage in the conservation process for three prominent conservation issues: acid rain in North America, global DDT contamination, and the overexploitation of African elephants for ivory. Variation in the order and magnitude of sector responses among the three issues emphasizes that there are multiple pathways to conservation success and that science is just one component. Our study highlights that while scientists can initiate the process, policy change does not occur in the absence of public interest. We suggest that the fate of conservation action is not solely determined by the scientific soundness of the conservation plan, but rather requires the engagement of scientists, public, and policy makers alike.